Lithuanian Institute of Physical Education
Homepage of the Lithuanian Institute of Physical Education with information and facts on structure, faculties, stuies, science, international relations, library, conferences, studies, links. Presently the Lithuanian Institute of Physical Education is a modern school with 6 faculties, 14 departments and 7 research laboratories. Bachelor's and Master's degrees, as well as Doctor's degrees can be obtained at the Institute. Teachers of physical education, coaches of different kinds of sports, specialists in kinesitherapy, health education and applied physical education and sport are trained at the Institute. Since 1995 specialists in sport and tourism management are also trained there. The pedagogical staff of the Institute numbers 107 teachers. 68 of them have scientific degrees or titles. 6 Hab.Doctors or Full Professors are employed at the Institute. The teachers and professors of the Institute are engaged in research in different fields of science. Among the more significant problems solved at the Institute are the following: "Physical Perfection of People of Different Age", "Training Methods and Preparedness Control of Athletes of Different Age and Skills", "Training of Specialists of Physical Education and Sport", etc.